The antimicrobial activity of Hypericum perforatum L. flower extract against food pathogens and its non-enzymatic antioxidant activity - Guler Ayhan; Okmen Gulten (Kragujevac Journal of Science)
Foodborne pathogens pose a significant hazard to food safety. Most cases of foodborne illnesses are caused by bacterial pathogens that have infiltrated the food chain at some point, from farm to kitchen. According to the World Health Organization (WHO), approximately one-third of individuals in developed countries are affected by foodborne pathogens each year. Although there are studies on Hypericum perforatum L. in the literature, research in Turkey remains limited. Therefore, the aim is to contribute to the literature by studying H. perforatum samples from the Yaraş region of Muğla province in Turkey. This study specifically aims to investigate the antimicrobial activities against foodborne pathogens and the antioxidant activity of H. perforatum in Muğla. The in vitro antimicrobial activities of flower components from plants grown in Mugla were evaluated using the disc diffusion method and broth dilution test. Additionally, the extracts underwent ABTS (2,2'-azinobis-(3-ethyl benzothiazoline-6-sulfonic acid)) free-radical testing to evaluate their antioxidant activity. The extract exhibited a maximum inhibition zone of 16 mm against Staphylococcus aureus and Listeria monocytogenes. Notably, S. aureus and L. monocytogenes demonstrated the lowest sensitivity to H. perforatum methanol extract (1625 µg/mL). The methanol extract displayed moderate antioxidant activity, with a 53% ABTS radical scavenging capacity. Consequently, the extracts of H. perforatum exhibited both antimicrobial and antioxidant potential.